2009
DOI: 10.1080/13547500903013664
|View full text |Cite
|
Sign up to set email alerts
|

Tumour necrosis factor-α and soluble Fas ligand as biomarkers in non-acetaminophen-induced acute liver failure

Abstract: The high levels of sFasL and TNF-alpha are associated with ALF. Following the trend of these cytokines can be useful in predicting death and timely referral to a transplant centre.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…16 And more recent studies have shown a correlation between CD95L levels and several human pathologies such as systemic lupus erythematosus, 17 toxic epidermal necrosis, acute pancreatitis, 18 acute hepatic failure 19 and burn injuries. 20 The influence of the initial phase of acute SCI on recovery or prognosis has not yet been researched.…”
Section: Discussionmentioning
confidence: 99%
“…16 And more recent studies have shown a correlation between CD95L levels and several human pathologies such as systemic lupus erythematosus, 17 toxic epidermal necrosis, acute pancreatitis, 18 acute hepatic failure 19 and burn injuries. 20 The influence of the initial phase of acute SCI on recovery or prognosis has not yet been researched.…”
Section: Discussionmentioning
confidence: 99%
“…In studies of non-NAFLD liver diseases, sFasL has been used as a biomarker of hepatocytic apoptosis with some success. Elevated serum levels of sFasL distinguished patients with acute liver failure from those with acute hepatitis E or with sepsis alone [16]. Serum levels of sFasL were also higher in patients with chronic but not acute hepatitis B and were highest in patients with the greatest degree of infection [17].…”
Section: Discussionmentioning
confidence: 99%
“…The balance between these two pathways determines the cell fate. Previous studies showed that elevated levels of serum TNF and over-expression of TNFR1 were observed and negatively correlated with the outcome in ALF patients [109,110,114], suggesting the pathogenic role of the TNF /TNFR1 signaling in human ALF. In parallel, treatment with adenovirus-mediated dominant negative form of the Fas-associated death domain (FADDdn), a downstream signaling molecule for Fas and TNFRs, inhibited the TNF /Galactosamine mediated hepatocellular apoptosis and significantly lowed the levels of serum transaminase in mice [114].…”
Section: Tumor Necrosis Factor (Tnf )/Tnfr Signalingmentioning
confidence: 96%
“…Fas may also exist as a soluble form (sFas), which can also be bound by FasL and antagonizes Fas-mediated apoptosis [108]. Notably, the expression of Fas is significantly up-regulated in apoptotic hepatocytes of ALF patients [109], and higher levels of serum FasL are also associated with the worse prognosis of ALF [110], indicating the potential involvement of Fas/FasL signaling in the pathogenesis of ALF., Song et al found that hydrodynamic tail vein injection of Fas-specific siRNA duplexes resulted in an efficient delivery of Fasspecific siRNA in majority of hepatocytes, dramatically down-regulation of Fas expression for more than 10 days in mouse hepatocytes [111]. Similarly, treatment with Fasspecific siRNA promoted the survival of animals with fulminant hepatitis induced by either intravenous injection of concanavalin (ConA) or intraperitoneal injection of agonistic Fas-specific antibody [111].…”
Section: Fas Ligang (Fasl)/fas Signalingmentioning
confidence: 98%